How to choose rib resection in minimally invasive lateral approach thoracolumbar junction corpectomy: radiographic analysis and case illustrations - Liu, Fengyu; Gu, Zhenfang; Sun, Xianze; Meng, Xianzhong (Frontiers in Surgery, 2025)
PurposeThe thoracolumbar junction (T10-L2) is a common site for spinal disorders such as fractures, tumors, and infections. Thoracolumbar vertebral corpectomy can be performed through the extracoelomic spaces approach (retropleural, retroperitoneal, and retrodiaphragmatic). The standard for selecting rib resection has not been described. We explored the criteria for rib resection in minimally invasive lateral approach thoracolumbar corpectomy through radiographic analysis and case illustrations.MethodsWe proposed the criteria for rib excision after reviewing the three-dimensional CT imaging of 300 patients' ribs. The vertebral body is divided obliquely into four zones. Ribs need to be removed when they overlap zones II and III, but not when they overlap zones I and IV. Surgery was performed according to this criteria to verify the feasibility of this criteria.ResultsFrom January 2024 to October 2024, 19 patients experienced minimally invasive lateral approach thoracolumbar corpectomy. Sixteen patients needed rib resection (the ninth rib resection: 4, the 10th rib resection: 12). Three patients did not require rib resection but underwent vertebra corpectomy through the intercostal. Two patients had pleural tear and were repaired during surgery. The VAS reduced from 8.9 ± 1.1 preoperatively to 1.2 ± 0.9 at final follow-up (P < 0.001).ConclusionsThis may be an appropriate criterion for determining rib resection in minimally invasive lateral approach thoracolumbar corpectomy. The vertebral body is divided obliquely into four zones. Ribs need to be removed when they overlap zones II and III, but not when they overlap zones I and IV.